Antimicrobial Effects and Composition of Essential Oils of Nepeta glomerata Montbret et Aucher ex Bentham (Lamiaceae) from Turkey - Toroglu, Sevil; Bagci, Eyup (Asian Journal of Chemistry, 2011)
In this study, antimicrobial activities and composition of essential oils of Nepeta glomerata Montbret et Aucher ex Bentham. were studied. The antimicrobial activity of this plant was evaluated by using disk diffusion method with Micrococcus luteus LA 2971, Listeria monocytogenes SCOTT A, Bacillus cereus EU, Enterococcus faecalis ATCC 15753, Pseudomonas aeruginosa ATCC 27853, Mycobacterium smegmatis RUT, Escherichia coli DM, Aeromonas hydrophila ATCC 7966, Yersinia enterocolitica AU 19, Bacillus brevis FMC 3, Corynebacterium xerosis UC 9165, Klebsiella oxytocica DC 113, Rhodotorula rubra DC 86, Saccharomyces cerevisiae WET 136 and Candida albicans DC 146. The results indicated that antimicrobial and antifungal activities were found in essential oils of Nepeta glomerata. The essential oil was analyzed by GC and GC/MS. Fifty components were identified representing 92.6 % of the oil. The main component of the Nepeta glomerata Montbret et Aucher ex Bentham was carvacrol (16.4 %).
Keywords: Essential oils; Nepeta glomerata Montbret et Aucher ex Bentham; Antibacterial activity; Antifungal activity; Composition